Possessive in Adverbial and Prepositive Locutions: en su contra ~ en contra suya (~ suyo) ~ en contra de él - Pato, Enrique (2022)
Thanks to linguistic corpus data (CORPES, Corpus del español) and the social network Twitter, this work revises previous descriptions about the use of the possessive in a series of prepositive and adverbial phrases (a gusto de, de parte de, en contra de, en vez de, en vista de, a modo de y en bien de), and actualizes various facts. In this way, it is verified that the most used possessive is always the prenominal (especially the third person). The postnominal possessive is possible, but as a minority option in all cases (with the third and first persons); documented above all in the colloquial register. The work also checks the agreement between the noun and the possessive. The data indicate that this agreement is respected, but examples of a lack of agreement are documented in colloquial registers (especially with the first person). Finally, regarding the complementation with the preposition de, it is verified that it is possible with the third person pronoun. However, the colloquial register also documents cases with other persons.